A revision of Discodon tricolor (Guérin-Méneville) and its mimics from the Atlantic forests of Brazil (Coleoptera: Cantharidae) - Biffi, Gabriel; Geiser, Michael (European Journal of Taxonomy, 2022)
Discodon tricolor (Guérin-Méneville, 1832) was thought to be a common species widely distributed in the Atlantic Forests of Brazil, yet showing morphological and chromatic variations. After examination of a large number of specimens from different regions of the Atlantic Forest biome, we found that Discodon tricolor actually represents a complex of many similar and sometimes sympatric species. Thirteen species in this complex are recognised as valid: Discodon tricolor, D. neoteutonum sp. nov., D. vanini sp. nov., D. obscurior Pic, 1906 stat. nov., D. lineaticorne sp. nov., D. aurimaculatum sp. nov., D. marginicolle sp. nov., D. tenuecostatum sp. nov., D. nigrocephalum Pic, 1949, D. tamoio sp. nov., D. viridimontanum sp. nov., D. crassipes Wittmer, 1952, and D. testaceipes Pic, 1930 stat. nov. The species Discodon albonotatum Pic, 1906 is confirmed as a synonym of D. tricolor, while the subspecies D. albonotatum obscurior and D. albonotatum testaceipes are elevated to specific status. The subgenus Acanthodiscodon Wittmer, 1952 is synonymised with Discodon Gorham, 1881. All the species are described and illustrated in detail and an identification key is provided. Despite being chromatically similar, the species show major morphological differences in their aedeagus and antennal structures, suggesting that they do not form a monophyletic clade. A potential mimicry ring involving these species of Discodon as well as other members of Cantharidae, Lampyridae, Cerambycidae and Belidae is discussed. Comments are made on the conservation of these species and their habitats within the Atlantic Forest biome.